Four-modality imaging of unmedicated subjects with schizophrenia: 18F-fluorodeoxyglucose and 18F-fallypride PET, diffusion tensor imaging, and MRI. (March 2022) - Buchsbaum, Monte S.; Mitelman, Serge A.; Christian, Bradley T.; Merrill, Brian M.; Buchsbaum, Bradley R.; Mitelman, Danielle; Mukherjee, Jogeshwar; Lehrer, Douglas S.
Highlights: Combination of functional and structural imaging modalities provides better prediction of diagnosis of schizophrenia than either of the two methods. 18 F-fallypride positron emission tomography in gray matter is more effective in predicting schizophrenia than any other tested modalities. Structural and functional modalities are comparable in predicting schizophrenia but use different brain regions. More than 40% of brain voxels are abnormal on at least one imaging modality. Abstract: Diminished prefrontal function, dopaminergic abnormalities in the striatum and thalamus, reductions in white matter integrity and frontotemporal gray matter deficits are the most replicated findings in schizophrenia. We used four imaging modalities ( 18 F-fluorodeoxyglucose and 18 F-fallypride PET, diffusion tensor imaging, structural MRI) in 19 healthy and 25 schizophrenia subjects to assess the relationship between functional (dopamine D2 /D3 receptor binding potential, glucose metabolic rate) and structural (fractional anisotropy, MRI) correlates of schizophrenia and their additive diagnostic prediction potential. Multivariate ANOVA was used to compare structural and functional image sets for identification of schizophrenia. Integration of data from all four modalities yielded better predictive power than less inclusive combinations, specifically in the thalamus, left dorsolateral prefrontal and temporal regions. Among the modalities, fractional anisotropy showed highest discrimination in white matter whereas 18 F-fallypride binding showed highest discrimination in gray matter. Structural and functional modalities displayed comparable discriminative power but different topography, with higher sensitivity of structural modalities in the left prefrontal region. Combination of functional and structural imaging modalities with inclusion of both gray and white matter appears most effective in diagnostic discrimination. The highest sensitivity of 18 F-fallypride PET to gray matter changes in schizophrenia supports the primacy of dopaminergic abnormalities in its pathophysiology.